Mechanistic Study on Electronic Excitation Dissociation of the Cellobiose-Na(+) Complex - Huang, Yiqun (J Am Soc Mass Spectrom, 2015)
The recent development of electron activated dissociation (ExD) techniques has opened the door for high-throughput, detailed glycan structural elucidation. Among them, ExD methods employing higher-energy electrons offer several advantages over low-energy electron capture dissociation (ECD), owing to their applicability towards chromophore-labeled glycans and singly charged ions, and ability to provide more extensive structural information. However, a lack of understanding of these processes has hindered rational optimization of the experimental conditions for more efficient fragmentation, as well as the development of informatics tools for interpretation of the complex glycan ExD spectra. Here, cellobiose-Na(+) was used as the model system to investigate the fragmentation behavior of metal-adducted glycans under irradiation of electrons with energy exceeding their ionization potential, and served as the basis on which a novel electronic excitation dissociation (EED) mechanism was proposed. It was found that ionization of the glycan produces a mixture of radical cations and ring-opened distonic ions. These distonic ions then capture a low-energy electron to produce diradicals with trivial singlet-triplet splitting, and subsequently undergo radical-induced dissociation to produce a variety of fragment ions, whose abundances are influenced by the stability of the distonic ions from which they originate.